Band engineering in nitrogen-rich AlGaNAs quaternary alloys. (July 2021) - Grodzicki, M.; Majchrzak, D.; Zdanowicz, E.; Benjamin, C.; Ciechanowicz, P.; Bell, G.R.; Kudrawiec, R.; Hommel, D.
Abstract: New alloys from the III-V family are presented. Undoped (0001)-oriented AlGaNAs epitaxial layers with 3%–16% Al and with constant As concentration equals 0.6% were grown by molecular beam epitaxy. Photoelectron spectroscopy, and secondary ion mass spectrometry confirm As incorporation into AlGaN and show that a small amount of As causes valence band (VB) modification. The VB maximum is shifted towards the Fermi level compared to AlGaN. Calculations based on the band anticrossing model shows the band gap of the AlGaNAs is reduced relative to AlGaN but its magnitude is higher than for GaNAs with the same As content. It is also suggested that the VB maximum in (Al)GaNAs alloys in the whole Al concentration in the diluted regime of As concentration is at the same energy on the absolute scale in the first approximation. This study shows the new potential of As in AlGaN-based alloy engineering. Highlights: New alloy from the III-V family - AlGaNAs (0001)-oriented - is presented. Small amount of As shifts valence band towards the Fermi level. VBM in (Al)GaNAs alloys is at the same position. Investigation is made by X-ray photoemission measurements.